Pond Conservation in Europe 2007
DOI: 10.1007/978-90-481-9088-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophyte diversity and physico-chemical characteristics of Tyrrhenian coast ponds in central Italy: implications for conservation

Abstract: Awareness of pond conservation value is growing all over Europe. Ponds are recognized as important ecosystems supporting large numbers of species and several rare and threatened aquatic plants, macroinvertebrates and amphibians. Notwithstanding ponds, particularly temporary ones, are still neglected in Italy. There are some gaps in our understanding of the macrophyte ecology and the conservation value of Mediterranean small still waters. Therefore, this study investigated the macrophyte communities and physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Farm ponds are usually considered artificial poor habitats, although it has been shown that sometimes they host a significant biodiversity, contributing to maintain rich trophic webs, from producers to consumers and decomposers [ 4 , 5 , 6 , 7 ]. Although biodiversity of these habitats is usually poorer than that of natural ones [ 8 , 9 ], it has been shown that the two groups are rather comparable as far as hydrophytes and red-listed species is concerned [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Farm ponds are usually considered artificial poor habitats, although it has been shown that sometimes they host a significant biodiversity, contributing to maintain rich trophic webs, from producers to consumers and decomposers [ 4 , 5 , 6 , 7 ]. Although biodiversity of these habitats is usually poorer than that of natural ones [ 8 , 9 ], it has been shown that the two groups are rather comparable as far as hydrophytes and red-listed species is concerned [ 9 ].…”
Section: Introductionmentioning
confidence: 99%